Pengaruh Implementasi Artificial Intelligence terhadap Kepuasan Pelanggan dalam Layanan Pengiriman Last-Mile Delivery pada Platform E-Commerce Shopee di Kota Bandung - Siska Karina (PT. AHLAL PUBLISHER NUSANTARA, 2026)
The expansion of e-commerce in Indonesia has intensified the operational demands of last-mile delivery, particularly in dense urban areas such as Bandung City. Shopee, as the dominant e-commerce platform in Southeast Asia, has integrated Artificial Intelligence (AI) into its delivery ecosystem through features such as real-time tracking, automated notifications, and AI-powered chatbots. Despite this adoption, empirical evidence on its effect on customer satisfaction in the Indonesian urban context remains limited. This study aims to analyze the effect of AI implementation on customer satisfaction in last-mile delivery services on the Shopee platform in Bandung City. A quantitative descriptive approach was employed with data collected from 82 respondents who are active Shopee customers in Bandung through a structured questionnaire using a Likert scale of 1–5. Data were analyzed using validity testing, reliability testing (Cronbach's Alpha), classical assumption tests, and simple linear regression using SPSS 26.0. Results show that all instrument items are valid (r > 0.3) and reliable (Alpha X = 0.859; Alpha Y = 0.784). The regression equation Y = 7.682 + 0.451X indicates that every one-unit increase in AI implementation perception increases customer satisfaction by 0.451 units. The coefficient of determination (R²) of 0.485 shows that 48.5% of customer satisfaction variance is explained by AI implementation. With t = 8.679 and Sig. = 0.000, the hypothesis is accepted: AI implementation has a positive and significant effect on customer satisfaction. The item